(untitled) (Journal of the College of Basic Education, 2023)
The city of Jabal Amel is considered one of the important Islamic cities in which religious schools spread and many scholars graduated from it who were credited with conveying the true image of the authentic Muhammadan Islam. It is important in spreading the principles of Muhammadan Islam, and we have discussed the life of the first martyr since his birth and then the schools in which he studied and the distinguished professors who were credited with the arrival of Sayyid Muhammad bin Makki to the prestigious scientific position, and then his scientific works and the most prominent students who studied at his hands until his martyrdom after the trial his mock up